Characterization of fish production and marketing practices under small-holder fish farming systems of eastern Kenya - Oyieng, Edwin P.; Charo, H.K.; Kahi, A.K.; Ojango, Julie M.K. (2013)
Aquaculture, a sub-component within the fisheries sector is a vital economic activity and livelihood component of rural communities living beside rivers and river floodplains in East Africa. It provides a good alternative source of income and proteins for rural communities. This study aimed to characterize fish production and marketing practices in smallholder farming systems under a national Economic Stimulus Programme (ESP) in the Eastern province of Kenya, and to determine the traits of economic importance to the farmers. Information was collated from 198 farmers, 13 traders and three key informants within Meru District of Eastern Province. The predominant species of fish reared was the Nile Tilapia, followed by the African Catfish and in some instances a combination of the two species were reared under polyculture. Good growth rate and survival of fish were noted to be the most important traits of economic importance to the farmers. Fish produced was mainly sold to the local community and within local markets. Traders, however, indicated that the demand for fish was much higher than the supply, hence also sourced fish from Lake Victoria in Nyanza for sale. It was also indicated that the taste of fish differed greatly depending on the source, with wild fish strains from Lake Victoria having a “sweeter” taste than the farmed strains. Strains of fish selected for improved growth and reproduction were not available for aquaculture. Feeds and feeding management of farmed fish was also a challenge. It was evident that there is a great need for supportive research on environmental impacts, productivity and quality of fish reared, and marketing of fish products within the riverine environments of Kenya. Key words: aquaculture, fish marketing, traits of economic importance